TRENDS AND INSIGHTS IN VISIONARY LEADERSHIP: A BIBLIOMETRIC ANALYSIS OF SCHOLARLY PUBLICATIONS FROM 2019 TO 2023 - Widiyanto, Setiawan; Setyarso; Mahmudi, Imam; Kiswara, Jajang; Urrasyidin, Andika; Riantanti, Diah Ika; Humardari, Dani; Wibowo, Yudho Arif (Journal of Social and Economics Research, 2024)
The study of visionary leadership has become increasingly significant as organizations navigate complex and evolving challenges. This paper presents a bibliometric analysis of scholarly publications on visionary leadership from 2019 to 2023, sourced from the Scopus database. The analysis reveals trends in publication output, identifies influential research contributions, and maps the thematic development of the field. Key findings highlight an increase in scholarly interest, with dominant themes including strategic vision, leadership competencies, and organizational change. Despite the wealth of research, gaps remain in empirical validation across diverse contexts, longitudinal studies, interdisciplinary approaches, and practical applications. The study underscores the need for more comprehensive research that bridges theoretical and practical insights, enhances cultural and global perspectives, and develops quantitative tools for assessing visionary leadership. By addressing these research gaps, the field can advance towards a deeper, more applicable understanding that supports both academic progress and practical leadership development. This paper serves as a foundational reference for scholars and practitioners, outlining current knowledge and future research directions.